An assessment model for virtual communities of practice: a study in the oil and gas industry. Issue 4 (1st November 2017) - Frank, Alejandro G.; Sander, Natália; Gastaldi, Luca; Madini, Emanuele; Corso, Mariano
Abstract: This paper proposes a model to assess the level of maturity in Virtual Communities of Practice (VCoPs). The model is based on a theoretical construction attained from the analysis of previous frameworks proposed in literature. Using this construction, we have proposed eight main organizational, managerial and technological levers to improve the performance of VCoPs. Additionally, the model presents the analysis of four performance metrics obtained from these VCoP management levers. The model presented can be used as a benchmarking tool for analysing how companies perform in their management of VCoPs. After developing the model, we applied it to a benchmarking study of four global oil and gas companies. Our results include a performance comparison among these companies as well as the main practices and technologies they use to achieve success in the management of VCoP.